Transient and Persistent Hypercalcaemia in Patients Treated by Maintenance Haemodialysis. Issue 5624 (19th October 1968) - Wing, A. J.; Curtis, J. R.; Eastwood, J. B.; Smith, E. K. M.; de Wardener, H. E.
Abstract : In a group of 32 patients with terminal renal failure the initial hypocalcaemia was corrected after two months' adequate maintenance haemodialysis. In seven patients hypercalcaemia occurred with a peak incidence after about six months' treatment. In six of these patients hypercalcaemia was transient and the plasma calcium became normal with haemodialysis alone. In one patient the hypercalcaemia was persistent and the plasma calcium reverted to normal only after subtotal parathyroidectomy. This patient had no radiological bone disease, a normal alkaline phosphatase, and no metastatic calcification of the soft tissues. It is concluded that in some patients with terminal renal failure treated with maintenance haemodialysis autonomy of the parathyroids becomes evident in the absence of bone disease or a raised plasma alkaline phosphatase, and that subsequently with continued dialysis there is a spontaneous involution towards normal parathyroid function.